Digital surveillance of Uyghur Turks - NARMANLIOĞLU, HALDUN (My University, 2022)
© 2022, Ahmet Yesevi University. All rights reserved.Digital surveillance technologies are among the most important oppressive government elements established by the People’s Republic of China in East Turkistan. The aim of the study is to reveal the digital surveillance that China has established on the Uyghur Turks through its technologies. The philosophical and ideological roots behind surveillance are also among the questions of the study. In this context, the historical perspective of China to others and the policies of ruling non-Chinese nations, and Chinese style of autonomous management are discussed. Later, the digital surveillance system established with a Confucian approach based on principles such as social order, obedience to the state and hierarchy was examined. For this purpose, academic studies and reports of non-governmental organizations on China’s surveillance-oriented technological infrastructure were scanned. The statements made by the Chinese government to the world public opinion and the news and comments reflected in the media were examined. According to the findings of the study, digital surveillance is one of the most important tools of China’s Uyghur policy. East Turkistan has been turned into an open-air prison through digital surveillance, leaving no free space for Uyghur Turks to practice their own identities.
Uygur Türkleri üzerinde dijital gözetim
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; Genel Sanat ve Beşeri Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Genel Sosyal Bilimler; General Arts and Humanities; Social Sciences & Humanities; General Social Sciences; digital surveillance. panopticon; liquid surveillance; People’s Republic of China; Social Credit System; Uyghur Turks